MISKONSEPSI SISWA PADA MATERI PERMUTASI DAN KOMBINASI DI KELAS XII SMA TARUNA BUMI KHATULISTIWA - Hendra Aulia R; Halini Halini; Asep Nursangaji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aimed to describe studentss misconceptions on permutation and combination material in 12th grade of SMA Taruna Bumi Khatulistiwa. The research method used in this study is a descriptive method in the form of case study research. The techniques used in this study are measurement techniques and direct communication techniques with data collection tools including four-tire diagnostic test sheet and interview guidance sheet. From the calculation results obtained that in the permutation material most students experienced misconceptions in item number 4 about 47% and wehereas in combination material many students experienced misconceptions in item number 3 about 24%. There are two forms of misconceptions that occur in students, namely systematic misconceptions and careless misconceptions. Based on the data obtained it can be concluded that students misconceptions on permutation and combination material in 12th grade of SMA Taruna Bumi Khatulistiwa are categorized into systematic misconceptions and careless misconceptions that are caused by incorrect reasoning. Keywords: Combination, Misconceptions, Permutation